The Effect of Retelling Technique to Students' EFL Learning in Narrating Past Events - Besral Besral; Luli Sari Yustina; Laura Renalsi (Fakultas Sastra Universitas Ekasakti, 2019)
Lack of students’ mastery of grammar and limited number of vocabulary have been identified assources of their low competence in EFL Learning to speak in West Sumatra Senior High Schools.Therefore, a constant effort to develop these two essential elements needs to be conducted especiallyin rural areas where advance technology of information is almost inaccessible. To deal with the issue,we have implemented Retelling technique to Grade X at Senior High School 1 Hiliran Gumanti. Agroup of science class (N=48) have been chosen to be the experimental and control groups. A typicaltreatment for the experimental class began with scaffolding the text. Discussion was focused onelements of text and in groups of four or five students, teacher encouraged the students to retellanother story. After 15 minutes discussions, each group was encouraged to retell the story startingfrom the first member (story-teller) and continued to the other members till the end of the story. Someextra pictures were accompanied the students to help them of the events. After several meetings, bothclasses were tested to retell another story. Post test scores of the groups were compared toinvestigate the difference. The finding showed that mean score of post test of experimental class was73.25, higher than control class (66.58). Meanwhile, standard deviation of experimental class washigher than control class (sd= 6.79>66.58). While t-calculated was 3.71 and t-table 1.678 witha=0.05 and degree of freedom 46 greater than t-table (3.71>1.678) meaning that students’ betterspeaking skills were mainly due to the application or effects of Retelling technique.